Equilibrium Hak Asasi Manusia Vis-À-Vis Kompilasi Hukum Islam; Quo Vadis Relevansi Modernitas dan Keindonesiaan - Sadari Sadari (SALAM: Jurnal Sosial dan Budaya Syar-i, 2015)
Abstract.This paper offers hududi studies in Islamic family law contained in the Islamic Law Compilation (KHI). Meanwhile, the hududi study itself is a process of desacralization as a form of KHI products to become progressive along with modernity and Indonesianness. To realize the quo vadis, this article carries out two ijtihad thoughts, namely, rejecting thoughts that have not heed hududi (limit) and strengthening the thinking of scholars who offer new ijtihad both on the plain of concept to methodological proposals. This encouraging thought came from a Syrian figure, namely Muhammad Shahrur, through the plausibility structure. His hududi study supports Nurcholish Madjid's idea of desacralization, so that he is able to carry out coherence between KHI and the fields of human rights, democracy, nation state, civil society, and constitutionalism. So this article supports the spirit of desacralization - apart from not giving up its sacredness - which is echoed by Nurcholish Madjid through his book on the theme: Islam, Kemodernan and Keindonesiaan. The source of the study of this article is KHI, while the way to read is by using the hududi paradigm, which is armed with the adagium sabat al-nass wa harakah al-muhtawa, meaning that the text is permanent (the text is permanent) and its content is constantly changing (the content moves). So that legal norms always derive from text-based liminality, whose axis of study is centered from text to context, not the opposite from context to text.Keywords: Equilibrium, Human Rights, KHI, and Indonesian-Modernity Abstrak. tulisan ini menawarkan studi hududi dalam hukum keluarga Islam yang terdapat dalam Kompilasi Hukum Islam (KHI). Sedangkan studi hududi itu sendiri merupakan proses desakralisasi sebagai wujud agar produk KHI menjadi progresif seiring dengan modernitas dan keindonesiaan. Untuk mewujudkan quo vadis tersebut, maka artikel ini melakukan dua ijtihad pemikiran yakni, menolak pemikiran yang belum mengindahkan hududi (limit, batas) dan menguatkan pemikiran para sarjana yang menawarkan ijtihad baru baik pada dataran konsep sampai pada tawaran metodologis.  Pemikiran yang menguatkan itu datang dari tokoh Syiria, yakni Muhammad Shahrur, lewat struktur kemasukakalan (plausibilitas structure). Studi hududi-nya mendukung ide dari Nurcholish Madjid tentang desakralisasi, sehingga mampu melakukan koherensi antara KHI dengan bidang HAM, demokrasi, nation state, civil society, dan konstitusionalisme.  Jadi artikel ini mendukung semangat desakralisasi – di samping tidak menanggalkan sakralisasinya – yang dikumandangkan oleh Nurcholish Madjid melalui bukunya yang bertema: Islam, Kemodernan dan Keindonesiaan. Sumber kajian artikel ini adalah KHI, sedangkan cara membaca dengan memakai paradigma hududi, yang berbekal pada adagium sabat al-nass wa harakah al-muhtawa, artinya teksnya tetap (the text is permanent) dan kandungannya terus berubah (the content moves). Sehingga norma hukum selalu bersumber pada liminalitas berbasis pada teks, yang poros kajiannya berpusat dari teks menuju konteks bukan sebaliknya dari konteks menuju teks.Kata Kunci: Equilibrium, HAM, KHI, dan Modernitas-Keindonesiaan